Sprouted Syrian Wheat in The Production of Arab Bread - Al-kateb, Mai Rajwan; Attra, Ramadan suliman; Sobh, Ahmad Mofeed Hasn (Journal of agricultural, environmental and veterinary sciences, 2021)
The research aims to study the optimum conditions for germination of Syrian hard wheat Cham 3, and to study the possibility of benefiting from sprouted wheat in fortifying Syrian Arab bread. The results were then treated statistically at the 95% reliability level using the Minitab program version 14. 0.It was evident through the statistical results that the optimum germination conditions for Syrian durum wheat Sham 3 is a temperature of 20 °C for a period of 4 days, as with these conditions the folic acid content reached 1. 75 mg / kg, which is approximately 13 times the folic acid content of meal wheat without sprouting (0. 135 mg / kg).By studying the rheological properties of flour and meal using Alveograph and Mixolab, it was noticed that germination led to a decrease in the strength of meal wheat. Where all the Alveograph indicators (P, L, G, W) and Mixolabs (C1, C2, C3, C4, C5, DDT) of germinated wheat significantly decreased compared to both flour and non-germinated meal. It was found that the possibility of benefiting from the Syrian sprouted wheat in fortifying the Syrian Arab bread, and the best percentage of adding crushed wheat sprouts to the Arabic bread is 40%, as it gave a sensory acceptable Arabic bread in terms of texture, separability, foldability and in terms of physical properties.The benefiting from the Syrian sprouted wheat in fortifying the Syrian Arab bread is possible, and the best percentage of adding sprouted wheat meal to the Arabic bread is 40%, as it gives a sensory acceptable Arabic bread in terms of texture, separability, foldability and in terms of physical properties.
Keywords: Sprouted Syrian Wheat; Arabic Bread; Rheological properties; Folic Acid